Bioeconomy for Sustainable Development. Issue 8 (2nd July 2019) - Aguilar, Alfredo; Twardowski, Tomasz; Wohlgemuth, Roland
Abstract : Bioeconomy is an emerging paradigm under which the creation, development, and revitalization of economic systems based on a sustainable use of renewable biological resources in a balanced way is rapidly spreading globally. Bioeconomy is building bridges between biotechnology and economy as well as between science, industry, and society. Biotechnology, from its ancient origins up to the present is at the core of the scientific and innovative foundation of bioeconomy policies developed in numerous countries. The challenges and perspectives of bioeconomies are immense, from resource‐efficient large‐scale manufacturing of products such as chemicals, materials, food, pharmaceuticals, polymers, flavors, and fragrances to the production of new biomaterials and bioenergy in a sustainable and economic way for a growing world population. Key success factors for different countries working on the bioeconomy vary widely from high‐tech bioeconomies, emerging diversified or diversified bioeconomies to advanced and basic primary sector bioeconomies. Despite the large variety of bioeconomies, several common elements are identified, which are simultaneously needed altogether. Abstract : Bioeconomy considers economic systems based on a sustainable use of renewable biological resources and is building bridges between biotechnology and economy as well as between science, industry and society. The challenges of bioeconomies range from resource‐efficient large‐scale manufacturing of products to the production of new biomaterials and bioenergy in a sustainable and economic way for a growing world population.